Reichard And Dickson, Eds., America On The World Stage - A Global Approach To U.S. History - Percy, Thomas (Teaching History: A Journal of Methods, 2009)
After reading America on the World Stage: A Global Approach to U.S. History, one might feel depressed and excited simultaneously. Depressed at how little you might be covering in your own survey course, but excited at the prospect of incorporating many of the concepts and teaching strategies contained in the book. Fourteen essays, all previously published in the Organization of American Historians Magazine of History, accompanied by teaching strategies that offer practical approaches to incorporate the essay’s content into the survey class urge historians to rethink American history in a global age and how they teach the survey course.